IMPLEMENTASI KURIKULUM MERDEKA BELAJAR KELAS XI DI SMA NEGERI 3 KENDARI PADA MATA PELAJARAN KIMIA - Ingki; Aceng Haetami; Dahlan (STKIP Subang, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum from the planning, execution, and evaluation stages, as well as to identify the constraints faced by eleventh-grade chemistry teachers at SMA Negeri 3 Kendari. The research method used was a descriptive qualitative approach, with data collected through questionnaires, interviews, observations, and documentation. The results indicated that the implementation of the Merdeka Curriculum fell into the